Positioning language proficiency: Interactions with a multilingual indigenous Ecuadorian. Issue 1 (13th September 2015) - Back, Michele
Abstract : In this article I work from the intersection of what Talmy (2010, 2011) termed the 'interview as social practice' and multilingual discourse to examine how researcher–participant subjectivities and notions of language proficiency were explored, assumed and resisted during my interactions with a participant I call Emilio. I use a discursive psychological approach to positioning (Davies and Harré 1990; Korobov 2010) and Bucholtz and Hall's (2004a, 2004b) tactics of intersubjectivity to highlight the subjectivities revealed in both the content of our interactions and the interactional resources used. Findings indicate that Emilio's and my perceptions of each other's proficiencies in English, Spanish, and Quichua (an Andean indigenous language) were modified through acts of positioning, with both interlocutors using tactics of adequation and distinction during a language history interview to either support or contest initial co-constructions of ourselves as proficient speakers of Quichua. Emilio's and my choice of languages also indexed our perceptions of the discursive activities in which we were engaged. With this analysis I demonstrate how language proficiency and language history interviews can become sites for resisting notions of proficiency among multilingual individuals, and the need to incorporate additional data to more comprehensively assess this proficiency.